Thermodynamic sea ice growth in the central Weddell Sea, observed in upward‐looking sonar data. Issue 3 (27th March 2015) - Behrendt, A.; Dierking, W.; Witte, H.
Abstract Upward‐looking sonar (ULS) data were used to analyze thermodynamic sea ice growth. The study was carried out for an ocean region in the central Weddell Sea, for which data of sea ice thickness variability and of the oceanic heat flux through the ice are rare. In the study area the contribution of sea ice deformation to vertical ice growth is relatively small in some years. This provides the opportunity to simulate thermodynamic sea ice growth considering the influence of a snow cover and of the oceanic heat flux. To this end, a modified version of Stefan's law was used. The resulting ice thickness variations were then compared with the ULS measurements. For the investigated cases, the best consistency between data and model results was obtained assuming a snow layer of less than 5 cm thickness and average oceanic heat fluxes between 6 and 14 W m−2. It is demonstrated that in conjunction with ice drift data and analytical models for thermal sea ice growth, ULS ice thickness measurements are useful for studying the seasonal cycle of growth and decay and for inferring the magnitude of the average oceanic heat flux under sea ice.